Gender Differentials in Unemployment Ins and Outs during the Great Recession in Spain - Sara de la Rica; Yolanda Fatima Rebollo-Sanz (Institute for the Study of Labor (IZA), 2015)
The Great Recession has had a disproportionately negative effect on working men compared to working women in many OECD countries and led to gender convergence in aggregate unemployment rates. In this paper we seek the sources of this recent convergence by using Social Security records on individuals to study the determinants of unemployment ins and outs over the course of a whole business cycle, i.e. 2000-2013. We focus on Spain a country hit hard by unemployment increases in downturns. Our results indicate that unemployment outs are crucial in understanding changes in unemployment rates in Spain. Furthermore, the huge drop in unemployment outs in the recession, particularly for men, has led to unprecedented levels of long-term unemployment, which has come to account for 64% of total unemployment. Negative state dependence emerges as a key barrier to job access for the long-term unemployed and hence the rate of unemployment is expected to remain high for many years, even if there is a strong recovery.
Keywords: J63; J64; J16; 330; state dependence; hazard rates; unemployment gross flows; gender differentials